A Psychoanalytic Study of Two Iranian Novels Based on Albert Bandura's Theory of Cognitive-social Learning - Farhad Hamedi; Kamran Pashaei Fakhri; Parvaneh Adelzadeh (Comparative Education Society of Iran ( CESIR), 2021)
Psychology and literature add to each other's richness through interrelationships. Psychological theories help to understand literary characters, and the literature provides concrete examples to support the views of psychologists. Based on this thought, the aim of the present study is to analyze the hermeneutics of two Iranian novels "Showhar-e Ahoo  Khanom" (Ahoo  Khoum's husband ) written by Mohammad Ali Afghani and " The Nocturnal Harmony of Wood Orchestra" by Reza Ghasemi based on Albert Bandura's theory of cognitive-social learning. The research method was a comparative type of qualitative content analysis and method of data collection was documentary. The research findings show that in both novels, the three key presuppositions of Bandura's theory, namely the interaction between people, environmental factors and key characters of the stories, are quite visible. The atmosphere of the stories also shows how observational learning is passed down from generation to generation. Another important finding is that the both novelists have shown that cognitive-social learning is impaired due to the conflict between tradition and modernism and has confused the characters of the stories. From an educational perspective, the present interpretation contributes to our understanding of the role of social change and the conflict between tradition and modernism in accelerating or disrupting the observational learning of the younger generation.